Cartografias coletivas : o torcedor cuiabano e a sua relação com a Seleção Brasileira de Futebol - Campos, Lairce Aleluia de (2015)
This dissertation studies the sociological profile cuiabano soccer fans, whose research was developed during the World Cup 2014, held in Brazil. It was observed the relation between such fans, the Brazilian national soccer team and its football clubs of the heart. Under anthropological and sociological perspective, the cheerleaders practices were mapped, built during the games in which the Brazilian team played. Keeping in view characterizing the subjects, it was necessary to know the cuiabano fans. Such an approach was made through three axes, the first of which refers to the socioeconomic profile; the second addresses the relationship of fans with soccer, and the third axis is the supporter of the bond with Brazilian clubs and with the Brazilian national football team. The theoretical constructs were based on studies and concepts of "tribe", developed by Maffesoli, "clubismo" in Damo and "twisted" by Toledo. We base the methodology in Survey research, both quantitative and qualitative, via questionnaires, semi-structured interviews, photographs and references. The results reveal that the fans who once found himself disengaged from the practice of going to the football stadium to honor the matches, he was encouraged to attend it.